Development of a lateral flow test strip for simultaneous detection of BT-Cry1Ab, BT-Cry1Ac and CP4 EPSPS proteins in genetically modified crops. (15th January 2021) - Zeng, Haijuan; Wang, Jinbin; Jia, Junwei; Wu, Guogan; Yang, Qianwen; Liu, Xiaofeng; Tang, Xueming
Highlights: A lateral flow test strip based on colloidal gold for multicomponent analysis was developed. GM crops containing BT-Cry1Ab, BT-Cry1Ac and CP4 EPSPS could be detected simultaneously. Visual detection limits for crops containing BT-Cry1Ab, Cry1Ac and CP4 EPSPS were 1%, 1% and 0.1%, respectively. The method was rapid (within 10 min), high-throughput, easy to operate and provided visible detection results. Abstract: A colloidal gold immunochromatographic strip (ICS) for simultaneous detection of multiple transgenic proteins, including CP4 EPSPS, BT-Cry1Ab and BT-Cry1Ac, was developed in this study. The sensitivity of the strip to the target protein was 5 ng/mL for CP4 EPSPS, 100 ng/mL for BT-Cry1Ab and Cry1Ac, respectively. Parallel analysis for maize, soybean, sugar beet and cotton showed the strip could detect 1% of transgenic content in crops containing BT-Cry1Ab and Cry1Ac, and, at least, 0.1% of content in crops containing CP4 EPSPS. The detection results for seed samples indicated the multicomponent analysis ICS had good accuracy. The analysis could be completed within 10 min and had the advantages of being high-throughput, easy to operate and visual detection. This is the first report of semi-quantitative ICS for detecting three transgenic proteins simultaneously. The developed approach may provide insights into the development of ICS for analyzing simultaneously multiple components in genetically modified crops.